PENGARUH BIPARTIT TERHADAP KOMUNIKASI DALAM PENYELESAIAN PERMASALAHAN HUBUNGAN INDUSTRIAL PANCASILA DI PT. KITADIN. - Ginting, - Parlin (EKONOMIA, 2019)
Effect of bipartite on communication in solving problems of Pancasila industrial relations at PT. Kitadin Tenggarong across from Kutai Kertanegara, under the guidance of Mr. LCA. Robin Jonathan as Advisor I, and Ms. Mardiana as Supervisor II. The background of this research is that communication between employers and trade unions is not optimal outside of bipartite meetings, bipartite meetings have not yet been scheduled, the need for regular communication between trade unions and employers and the need for socialization before changing existing company policies. The purpose of this study was to determine how the influence of bipartite on communication in solving the problems of Pancasila Industrial Relations at PT. Kitadin. The theoretical basis used in this study is the management of human resources about science and art regulating relationships and the role of labor to be effective and efficient to help realize the goals of the company, employees and society. This research uses quantitative methods using data from 30 questionnaire samples from 145 employees as the object of research. The analytical tool used in this study is to use path analysis with quantitative analysis including validity and reliability tests, classical assumption tests, hypothesis testing through t test, F test, and Sobel test. Partially based on the results of t test the variables in this study have an effect positive and significant for Pancasila industrial relations in solving problems at PT. Kitadin